Physical Activity, Sedentary Behavior, and Health States of University Students During the First Wave of COVID-19 Community Quarantine in the Philippines - Cruz, Angelita B.; Cando, Jean Marie; Kim, Hyun-Duck (Frontiers in Education, 2022)
This study examined the impact of the first wave of COVID-19 pandemic community quarantine on university students’ physical activity (PA) levels, sedentary behaviors, and health states in the Philippines. A total of 1042 university students completed the International Physical Activity Questionnaire (IPAQ) short version and rated their health states using an online survey. The Wilcoxon signed-rank test and Spearman’s rank correlation coefficient were used for statistical analyses to compare changes in PA and sedentary behaviors (prior to and during COVID-19) and determine the relationship between changes in the total volume of PA and various health states of male and female students respectively. Overall, the total PA of students significantly declined during COVID-19 compared to before the pandemic. Total PA of male students did not significantly change during COVID-19 but did for females. Female students’ sitting time significantly reduced during weekdays. Changes in PA was associated with different aspects of health, particularly for female students, during the COVID-19 community quarantine. The finding extends the literature about the impact of COVID-19 on students’ PA and health and underscores the importance of PA as a way in alleviating negative perceptions related to health in university students despite the implemented community quarantine regulations.